Policy and Institutional Frameworks for Sustainable Livelihoods of Indigenous Communities in Jhaekhand - Shandilya, Shivendra (Indian Journal of Political Science)
The present study delves into an analysis of the policy and institutional frameworks that have been implemented to foster sustainable livelihoods among indigenous communities residing in the state of Jharkhand, India. Scheduled Tribes, commonly known as indigenous communities, have encountered socioeconomic marginalisation and environmental obstacles throughout history, resulting in negative impacts on their well- being and livelihoods. The research commences with a comprehensive exposition of the native populations in Jharkhand, emphasising their cultural importance. The statement underscores the necessity of policy interventions and institutional support to tackle the challenges related to the sustenance of these communities and guarantee their enduring progress. This study investigates extant policies and programmes that have been put in place by the state government and other pertinent institutions with the aim of enhancing the well-being of indigenous communities. This study provides a critical analysis of the strengths, weakness, and gaps in existing frameworks. The analysis takes into account various factors such as land rights, access to natural resources, skill development, entrepreneurship, social inclusion, and environmental sustainability. The present study's results augment the pre- existing understanding of policy and institutional frameworks concerning sustainable development within indigenous communities located in Jharkhand. - Reproduced
Keywords: Indigenous community, institutional framework, Jharkhand, Policy